Relationship between Mayo endoscopic score and histological scores in ulcerative colitis: A prospective study. Issue 3 (2nd October 2019) - Shah, Jimil; Dutta, Usha; Das, Ashim; Sharma, Vishal; Mandavdhare, Harshal; Sharma, Pankaj; Kalsi, Dimple; Popli, Priyanka; Kochhar, Rakesh
Abstract : Background: The Mayo endoscopic score (MES) remains the most commonly used index in clinical practice, as well as in various clinical trials. Recently, two validated histological indices (Nancy Index [NI] and Robert Histological Index [RHI]) have been developed for ulcerative colitis (UC). We aim to study the relationship between MES with NI, RHI, and the established Geboes Index (GI) in patients with UC. Methods: This was a prospective single‐center study. MES was documented from the most involved area. Biopsy was taken from the same area and reported by a single gastrointestinal histopathologist who was blinded to the endoscopic score. Histological activity was reported using GI, NI, and RHI. Statistical analysis was performed using Spearman's correlation coefficient and Cohen's kappa coefficient using SPSS version 23. Results: Median age of patients with UC ( n = 96) was 36 years. Seventeen patients were in endoscopic remission (MES 0/1). Correlation coefficient between MES and GI/NI/RHI was only weak to moderate (rho = 0.381/0.389/0.442, respectively; P  < 0.001 for all three correlations). In patients with endoscopic mucosal healing ( n = 17), the agreement coefficient between MES and GI/RHI was weak ( κ = 0.253/0.336, respectively; P = 0.001 for both agreements). However, there was no significant agreement coefficient between MES and NI ( P = 0.573). Conclusion: MES moderately correlated with histological scores. RHI had the best correlation with MES among all histological indices. Endoscopic mucosal healing is not strongly correlated with histological healing. Histological examination should be performed even in patients with mucosal healing to detect ongoing histological activity. Abstract : In the era of mucosal and histological healing, it is of utmost importance to understand the relationship between endoscopic and histological scores. In our study, we have shown that the endoscopic score is only moderately correlated with histological scores. Agreement between endoscopic and histological remission is also weak. A better endoscopic scoring system is needed for defining endoscopic remission.